How do Europeans perceive their healthcare system?: patterns of satisfaction and preference for state involvement in the field of healthcare - Wendt, Claus; Kohl, Jürgen; Mischke, Monika; Pfeifer, Michaela (European sociological review, 2010)
In this article we analyse the relationship between the institutional set-up of healthcare systems and patterns of public support. Two dimensions are distinguished, namely, state responsibility for healthcare provision and satisfaction with healthcare systems. Using data on 14 European countries from the Eurobarometer survey, we find only small effects of institutional indicators on preferences for a strong role of the state. Almost everywhere in Europe, there is high public support for state responsibility in healthcare. Satisfaction with the healthcare system, in contrast, is more strongly related to specific institutional arrangements. In healthcare systems with lower levels of expenditure, fewer general practitioners and higher co-payments, the overall level of satisfaction is lower. This is especially the case in Southern Europe where more pronounced differences between social groups also become apparent. In contrast, healthcare systems with a long tradition of comprehensive coverage regardless of occupation or income seem to generate rather homogenous attitudinal patterns. These characteristics hold for the Scandinavian systems and for the British National Health Service, and therefore, these healthcare systems still seem to live up to the promise of treating all members of the society equally. Countries with high levels of expenditure, high density of general practitioners, and free choice of doctors, which is mainly the case in Social Health Insurance systems, finally, show the highest levels of satisfaction but also more pronounced differences between social classes.